2017
DOI: 10.1007/s00442-017-4032-z
|View full text |Cite
|
Sign up to set email alerts
|

Heated communities: large inter- and intraspecific variation in heat tolerance across trophic levels of a soil arthropod community

Abstract: Temperature extremes are predicted to increase in frequency, intensity and duration under global warming and are believed to significantly affect community composition and functioning. However, the effect of extreme climatic events on communities remains difficult to predict, especially because species can show dissimilar responses to abiotic changes, which may affect the outcome of species interactions. To anticipate community responses we need knowledge on within and among species variation in stress toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 86 publications
1
46
1
Order By: Relevance
“…CT max values ranged from 52 to 55°C on average. These values are likely comparable to the CT max of 51-52°C found for desert-dwelling spiders (Franken et al, 2018;van den Berg et al, 2015), which were measured under a slower ramping rate, and higher than species found in the Namib, assessed using a non-ramping method (Lubin and Henschel, 1990).…”
Section: Evidence For Brett's Rulesupporting
confidence: 77%
“…CT max values ranged from 52 to 55°C on average. These values are likely comparable to the CT max of 51-52°C found for desert-dwelling spiders (Franken et al, 2018;van den Berg et al, 2015), which were measured under a slower ramping rate, and higher than species found in the Namib, assessed using a non-ramping method (Lubin and Henschel, 1990).…”
Section: Evidence For Brett's Rulesupporting
confidence: 77%
“…juveniles and larvae) which by definition are not yet fully developed, both show improved heat tolerance with increasing body mass, contrasting with impaired heat tolerance in adults (Figure S9, electronic supplementary material). Along the same line, in a study looking at intraspecific variation in body mass, CTmax improved with body mass in juveniles of a spider species, but deteriorated with size of adults in species of Hemiptera and Collembola [38]. Thus, an oxygen-based mechanism could play a role in heat tolerance but appears to be more relevant for water-breathers and on longer timescales: i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While studies to date hint at a possible size-dependence of thermal limits, no studies have tested this possibility comprehensively. In fact, most studies have focused on one or a few species and although these often find no effect of body mass when included as a covariate in analyses, thermal tolerance limits (heat tolerance rather than cold tolerance) are more frequently reported to decrease rather than increase with increasing body mass [35–38]. In an effort to address this knowledge gap regarding how body mass modulates the response to the temperature in ectotherms, we take advantage of the large body of literature and created a database of upper and lower thermal limits supplemented with biological information of 510 species.…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge in soils is to track such phenological shifts of species in response to warming given the complexity of the soil habitat and a high density of species [33]. The indication of trophic mismatches in soils in response to climate warming thus mainly comes from studies that have shown differential responses among communities of different trophic levels of brown food webs [4,35,36], potentially also owing to interspecific variation in thermal tolerance between predators and prey communities [37]. These differences in responses are often measured in terms of microbial biomass and soil thermal tolerances Figure 1.…”
Section: Climate Change and Trophic Mismatches In Food Websmentioning
confidence: 99%